Dual-ion battery using graphitic carbon and Li4Ti5O12: Suppression of gas formation and increased cyclability. (1st February 2020) - Nozu, Ryutaro; Suzuki, Eiko; Kimura, Okitoshi; Onagi, Nobuaki; Ishihara, Tatsumi
Abstract: Discharge performance of dual-ion battery (DIB) consisting of graphitic carbon and Li4 Ti5 O12 for positive and negative electrodes, respectively, were studied. Effects of electrolyte on cycle performance and gas formation were also studied. Reasonable discharge capacity (>65 mA h/g-positive electrode) was achieved; however, capacity fading significantly occurred when LiPF6 + LiBF4 in DMC/MEC/PC was used for electrolyte. The gas formation during charge and discharge cycles by electrolyte decomposition affects the practical use of DIB. Therefore, it is important to understand the mechanism of gas formation and the cycle performance degradation during charge and discharge cycles of DIB. Decomposition of electrolyte on positive electrode was related to the potential increase of negative electrode. In contrast, electrolyte decomposition is much suppressed by using LiBF4 supporting acid for electrolyte, and this can be assigned to the stable charge and discharge performance of negative electrode. Therefore, although the initial capacity was decreased with cycle number, LiBF4 − dissolved electrolyte was stable and the cell showed stable cycle performance with negligible small gas formation. Our findings also showed that the reversibility of charging and discharging negative electrode was poor under DIB condition unlike with the LIB system.